Geological study of Aqra Formation for possible use as Portland cement in Chwarta-Mawat area Sulaimani – Iraqi Kurdistan Region - Fatah, Chro Muhammad; Ahmad, Kamal Haji Karim; Mirza, Tola Ahmad (Sulaimani Journal for Pure and Applied Sciences, 2020)
A succession of highly fossiliferous limestone of Aqra Formation is studied geochemically and strati graphically. The outcrops of succession have the thickness, width and length of about 160, 1500 and 30000 meters respectively. The outcrops located in the Chwarta-Mawat area in the Kurdistan Region, northeastern Iraq. An exposed section is selected for field and lab studies, and inspected by eyes and hand lenses. Twelve samples are taken for geochemical analyses and indication of possible use of the succession for Portland cement production. The analysis shows that the whole succession is consist of calcitic limestone which contains more than 95 % of CaCO3, less than 1% MgO, Fe2O3, Al2O3, Na2O, and K2O. The analyses show that the limestone is high grade limestone which is very suitable for Portland cement production. In the area there is good quality and quantity of claystone as correctors’ materials for the clinker. These claystone belong to the unit one of the Red Bed Series which extensively exposed directly to the north and northeast of the sampled section of the Aqra Formation. The results show that the Aqra limestone can be used in cement industry. The Ratios of the alumina modulus (AM), Hydraulic modulus (HM), silica modulus (SM) and lime saturation Factor (L.S.F) were also calculated. It was found that these ratios of some samples are compatible to Standards Specifications and other are not therefore some quantity of claystone from lower part of Red Bed Series were added to compensate for the percentage of silica, alumina and iron oxides for the suitable limestone as well as lowering the LSF values to acceptable ranges. It was found that most of the clinker phases of the studied samples have a good agreement with these typical constituents of normal Portland cement.
Keywords: Aqra Formation; Mawat area; Late Cretaceous carbonate; Portland cement; Chemical Composition; Clinker phases